Open Access

Some further extensions of absolute Cesàro summability for double series

Journal of Inequalities and Applications20132013:144

https://doi.org/10.1186/1029-242X-2013-144

Received: 14 December 2012

Accepted: 20 March 2013

Published: 2 April 2013

Abstract

In a recent paper [Savaş and Rhoades in Appl. Math. Lett. 22:1462-1466, 2009], the authors extended the result of Flett [Proc. Lond. Math. Soc. 7:113-141, 1957] to double summability. In this paper, we consider some further extensions of absolute Cesàro summability for double series.

MSC:40F05, 40G05.

Keywords

absolute summabilitybounded operatorCesáro matrixdouble seriesHausdorff matrix
Let m = 0 n = 0 a m n be an infinite double series with real or complex numbers, with partial sums
s m n = i = 0 m j = 0 n a i j .
For any double sequence ( x m n ) we shall define
Δ 11 x m n = x m n x m + 1 , n x m , n + 1 + x m + 1 , n + 1 .
Denote by A k 2 the sequence space defined by
A k 2 = { ( s m n ) m , n = 0 : m = 1 n = 1 ( m n ) k 1 | a m n | k < ; a m n = Δ 11 s m 1 , n 1 }

for k 1 .

A four-dimensional matrix T = ( t m n i j : m , n , i , j = 0 , 1 , ) is said to be absolutely k th power conservative for k 1 , if T B ( A k 2 ) , i.e., if
m = 1 n = 1 ( m n ) k 1 | Δ 11 s m 1 , n 1 | k < ,
then
m = 1 n = 1 ( m n ) k 1 | Δ 11 t m 1 , n 1 | k < ,
where
t m n = i = 0 j = 0 t m n i j s i j ( m , n = 0 , 1 , ) .
A double infinite Cesáro matrix C ( α , β ) is a double infinite Hausdorff matrix with entries
h m n i j = E m i α 1 E n j β 1 E m α E n β ,
where
E m α = ( m + α m ) = Γ ( α + m + 1 ) Γ ( m + 1 ) Γ ( α + 1 ) m α Γ ( α + 1 ) .
The series a m n is said to be summable | C ( α , β ) | k , k 1 , α , β > 1 , if (see [1])
m = 1 n = 1 ( m n ) k 1 | Δ 11 σ m 1 , n 1 α β | k < ,
(1)
where σ m n α β denotes the mn-term of the C ( α , β ) transform of a sequence ( s m n ) ; i.e.,
σ m n α β = 1 E m α E n β i = 0 m j = 0 n E m i α 1 E n j β 1 s i j .
(2)

Quite recently, Savaş and Rhoades [2] extended the result of Flett [3] to double summability. Their theorem is as follows.

Theorem 1 Let α γ > 1 , β δ > 1 , and m n a m n be a double series with partial sums s m n . If m n a m n is | C ( γ , δ ) | k -summable, then it is also | C ( α , β ) | k -summable, k 1 .

It then follows that if one sets γ = δ = 0 , then C ( α , β ) B ( A k 2 ) for each α , β 0 . In this paper, we consider some further extensions of absolute Cesàro summability for double series.

We shall use the following lemmas.

Lemma 1 If θ > 1 , ϕ > 1 , θ φ > 0 and ϕ ψ > 0 , then
m = i n = j E m i φ E n j ψ m n E m θ E n ϕ = 1 i j E i θ φ 1 E j ϕ ψ 1 .
(3)
Proof For α > 1 , n 1 since
1 E n α = 0 1 ( 1 x ) α x n 1 d x
and
( 1 x ) α = n = 0 E n α 1 x n ,
we obtain
m = i n = j E m i φ E n j ψ m n E m θ E n ϕ = m = i E m i φ m E m θ n = 0 E n ψ ( n + j ) E n + j ϕ = m = i E m i φ m E m θ n = 0 E n ψ 0 1 ( 1 x ) ϕ x n + j 1 d x = m = i E m i φ m E m θ 0 1 ( 1 x ) ϕ x j 1 ( n = 0 E n ψ x n ) d x = 0 1 ( 1 x ) ϕ ψ 1 x j 1 d x m = 0 E m φ ( m + i ) E m + i θ = 1 j E j ϕ ψ 1 m = 0 E m φ 0 1 ( 1 x ) θ x m + i 1 d x = 1 j E j ϕ ψ 1 0 1 ( 1 x ) θ φ 1 x i 1 d x = 1 i j E i θ φ 1 E j ϕ ψ 1 .

 □

For single series, Lemma 1 due to Chow [4].

Lemma 2 Let 1 k r < and α , β > 1 . For i , j 1 , let
A i j = A i j ( α , β ) = m = i n = j | E m i α 1 | r / k | E n j β 1 | r / k m n ( E m α ) r / k ( E n β ) r / k .
(4)
Then, if k = r ,
A i j = { O ( i α 1 j β 1 ) , if α , β < 0 , O ( i α 1 j 1 ) , if α < 0 , β 0 , O ( i 1 j β 1 ) , if α 0 , β < 0 , O ( i 1 j 1 ) , if α , β 0 .
(5)
If k < r < , then
A i j = { O ( i α r k 1 j β r k 1 ) , if α < 1 k / r , β < 1 k / r , O ( i α r k 1 j r k log j ) , if α < 1 k / r , β = 1 k / r , O ( i α r k 1 j r k ) , if α < 1 k / r , β > 1 k / r , O ( i α r k 1 j β r k 1 log i ) , if α = 1 k / r , β < 1 k / r , O ( i r k j r k log i log j ) , if α = 1 k / r , β = 1 k / r , O ( i α r k 1 j r k log i ) , if α = 1 k / r , β > 1 k / r , O ( i r k j β r k 1 ) , if α > 1 k / r , β < 1 k / r , O ( i r k j β r k 1 log j ) , if α > 1 k / r , β = 1 k / r , O ( i r k j r k ) , if α > 1 k / r , β > 1 k / r .
(6)
Proof Since | E n α | K ( α ) n α for all α, and E n α M ( α ) n α for α > 1 , where K ( α ) and M ( α ) are positive constants depending only on α, if k < r < , then
A i j = O ( 1 ) m = i n = j m α r k 1 n β r k 1 ( m i + 1 ) ( α 1 ) r k ( n j + 1 ) ( β 1 ) r k = O ( 1 ) ( m = i 2 i 1 m α r k 1 ( m i + 1 ) ( α 1 ) r k + m = 2 i m α r k 1 ( m i + 1 ) ( α 1 ) r k ) × ( n = j 2 j 1 n β r k 1 ( n j + 1 ) ( β 1 ) r k + n = 2 j n β r k 1 ( n j + 1 ) ( β 1 ) r k ) = O ( 1 ) ( i α r k 1 m = i 2 i 1 ( m i + 1 ) ( α 1 ) r k + m = 2 i m r k 1 ) × ( j β r k 1 n = j 2 j 1 ( n j + 1 ) ( β 1 ) r k + n = 2 j n r k 1 ) = O ( 1 ) i α r k 1 j β r k 1 m = 1 i n = 1 j m ( α 1 ) r k n ( β 1 ) r k + O ( 1 ) i α r k 1 j r / k m = 1 i m ( α 1 ) r k + O ( 1 ) i r / k j β r k 1 n = 1 j n ( β 1 ) r k + O ( 1 ) ( i j ) r / k .

According as ( α 1 ) r k and ( β 1 ) r k = 1 , < 1 or > 1 , we have (6). The case k = r is proved similarly. □

For single series, Lemma 2 due to Mehdi [5].

We now prove the following theorem.

Theorem 2 Let r k 1 .

(i) It holds that C ( α , β ) ( A k 2 , A r 2 ) for each α , β > 1 k / r .

(ii) If α , β = 1 k / r and the condition m = 1 n = 1 ( m n ) k 1 log m log n | a m n | k = O ( 1 ) is satisfied then C ( α , β ) ( A k 2 , A r 2 ) .

(iii) If the condition m = 1 n = 1 m k + ( 1 α ) r k 2 n k + ( 1 β ) r k 2 | a m n | k = O ( 1 ) is satisfied then C ( α , β ) ( A k 2 , A r 2 ) for each k / r < α , β < 1 k / r .

(iv) If β = 1 k / r and the condition m = 1 n = 1 m k + ( 1 α ) r k 2 n k 1 log n | a m n | k = O ( 1 ) is satisfied then C ( α , β ) ( A k 2 , A r 2 ) for each k / r < α < 1 k / r .

(v) If the condition m = 1 n = 1 m k + ( 1 α ) r k 2 n k 1 | a m n | k = O ( 1 ) is satisfied then C ( α , β ) ( A k 2 , A r 2 ) for each k / r < α < 1 k / r and β > 1 k / r .

(vi) If α = 1 k / r and the condition m = 1 n = 1 m k 1 n k + ( 1 β ) r k 2 log m | a m n | k = O ( 1 ) is satisfied then C ( α , β ) ( A k 2 , A r 2 ) for each k / r < β < 1 k / r .

(vii) If the condition m = 1 n = 1 m k 1 n k 1 log m | a m n | k = O ( 1 ) is satisfied then C ( α , β ) ( A k 2 , A r 2 ) for each α > 1 k / r , β < 1 k / r .

(viii) If the condition m = 1 n = 1 m k 1 n k + ( 1 β ) r k 2 | a m n | k = O ( 1 ) is satisfied then C ( α , β ) ( A k 2 , A r 2 ) for each α > 1 k / r and k / r < β < 1 k / r .

(ix) If β = 1 k / r and the condition m = 1 n = 1 m k 1 n k 1 log n | a m n | k = O ( 1 ) is satisfied then C ( α , β ) ( A k 2 , A r 2 ) for each α > 1 k / r .

Proof We shall show that ( σ m n α β ) A r 2 , i.e.,
m = 1 n = 1 ( m n ) r 1 | Δ 11 σ m 1 , n 1 α β | r < .
Let τ m n α β denote the mn-term of the C ( α , β ) -transform in terms of ( m n a m n ) , i.e.,
τ m n α β = 1 E m α E n β i = 1 m j = 1 n E m i α 1 E n j β 1 i j a i j .
For α , β > 1 , since
τ m n α β = m n ( σ m n α β σ m , n 1 α β σ m 1 , n α β + σ m 1 , n 1 α β ) ,
to prove the theorem, it will be sufficient to show that
m = 1 n = 1 ( m n ) 1 | τ m n α β | r < .
(7)
Using Hölder’s inequality, we have
m = 1 n = 1 1 m n | τ m n α β | r = m = 1 n = 1 1 m n | 1 E m α E n β i = 1 m j = 1 n E m i α 1 E n j β 1 i j a i j | r m = 1 n = 1 1 m n ( E m α ) r ( E n β ) r { i = 1 m j = 1 n | E m i α 1 | | E n j β 1 | i k j k | a i j | k } r / k × { i = 1 m j = 1 n | E m i α 1 | | E n j β 1 | } ( k 1 ) r / k .
Since
i = 1 m j = 1 n | E m i α 1 | | E n j β 1 | = ( | E 0 α 1 | + i = 1 m 1 | E m i α 1 | ) ( | E 0 β 1 | + j = 1 n 1 | E n j β 1 | ) = ( | E 0 α 1 | + | i = 1 m 1 E m i α 1 | ) ( | E 0 β 1 | + | j = 1 n 1 E n j β 1 | ) = ( | E 0 α 1 | + | i = 0 m E m i α 1 E m α 1 E 0 α 1 | ) × ( | E 0 β 1 | + | j = 0 n E n j β 1 E n β 1 E 0 β 1 | ) = ( | E 0 α 1 | + | E m 1 α E 0 α 1 | ) ( | E 0 β 1 | + | E n 1 β E 0 β 1 | ) ,
and using the fact that
| E m 1 α E m α | = O ( 1 ) and | E n 1 β E n β | = O ( 1 ) ,
we obtain
m = 1 n = 1 1 m n | τ m n α β | r m = 1 n = 1 ( E m α ) ( k 1 ) r / k ( E n β ) ( k 1 ) r / k m n ( E m α ) r ( E n β ) r × { i = 1 m j = 1 n | E m i α 1 | | E n j β 1 | i k j k | a i j | k } r / k m = 1 n = 1 ( E m α ) r / k ( E n β ) r / k m n × { i = 1 m j = 1 n | E m i α 1 | | E n j β 1 | ( i j ) 1 k / r + k 2 / r | a i j | k 2 / r ( i j ) ( r k ) + k ( r k ) / r | a i j | k ( r k ) / r } r / k .
Applying Hölder’s inequality with indices r / k , r / ( r k ) , we deduce that
m = 1 n = 1 1 m n | τ m n α β | r m = 1 n = 1 ( E m α ) r / k ( E n β ) r / k m n i = 1 m j = 1 n | E m i α 1 | r / k | E n j β 1 | r / k ( i j ) k 1 + r / k | a i j | k × { i = 1 m j = 1 n ( i j ) k 1 | a i j | k } ( r k ) / k .
Since ( s m n ) A k 2 , we have
m = 1 n = 1 1 m n | τ m n α β | r = O ( 1 ) i = 1 j = 1 ( i j ) k 1 | a i j | k ( i j ) r / k m = i n = j | E m i α 1 | r / k | E n j β 1 | r / k m n ( E m α ) r / k ( E n β ) r / k .
(i) From Lemma 1, if α , β > 1 k / r , then
m = i n = j ( E m i α 1 ) r / k ( E n j β 1 ) r / k m n ( E m α ) r / k ( E n β ) r / k = ( i j ) 1 1 E i r k 1 E j r k 1 = O ( ( i j ) r / k ) .
Therefore, for the case α , β > 1 k / r , we have
m = 1 n = 1 1 m n | τ m n α β | r = O ( 1 ) i = 1 j = 1 ( i j ) k 1 | a i j | k ( i j ) r / k ( i j ) r / k = O ( 1 ) i = 1 j = 1 ( i j ) k 1 | a i j | k = O ( 1 ) ,

since ( s m n ) A k 2 .

(ii) If α , β = 1 k / r , from Lemma 2, then
m = i n = j | E m i α 1 | r / k | E n j β 1 | r / k m n ( E m α ) r / k ( E n β ) r / k = O ( i r k j r k log i log j ) .
Hence,
m = 1 n = 1 1 m n | τ m n α β | r = O ( 1 ) i = 1 j = 1 ( i j ) k 1 log i log j | a i j | k = O ( 1 ) .
(iii) If k / r < α , β < 1 k / r , from Lemma 2, then
m = i n = j | E m i α 1 | r / k | E n j β 1 | r / k m n ( E m α ) r / k ( E n β ) r / k = O ( i α r k 1 j β r k 1 ) ,
and then
m = 1 n = 1 1 m n | τ m n α β | r = O ( 1 ) i = 1 j = 1 ( i j ) k + r / k 1 i α r k 1 j β r k 1 | a i j | k = O ( 1 ) i = 1 j = 1 i k + ( 1 α ) r k 2 j k + ( 1 β ) r k 2 | a i j | k = O ( 1 ) .
(iv) If β = 1 k / r and k / r < α < 1 k / r , from Lemma 2, then
m = i n = j | E m i α 1 | r / k | E n j β 1 | r / k m n ( E m α ) r / k ( E n β ) r / k = O ( i α r k 1 j r k log j ) ,
therefore, we have
m = 1 n = 1 1 m n | τ m n α β | r = O ( 1 ) i = 1 j = 1 ( i j ) k 1 | a i j | k ( i j ) r / k i α r k 1 j r k log j = O ( 1 ) i = 1 j = 1 i k + ( 1 α ) r k 2 j k 1 log j | a i j | k = O ( 1 ) .
(v) If k / r < α < 1 k / r and β > 1 k / r , then
m = 1 n = 1 1 m n | τ m n α β | r = O ( 1 ) i = 1 j = 1 ( i j ) k 1 | a i j | k ( i j ) r / k i α r k 1 j r k = O ( 1 ) i = 1 j = 1 i k + ( 1 α ) r k 2 j k 1 | a i j | k = O ( 1 ) ,

by using Lemma 2.

(vi) If α = 1 k / r and k / r < β < 1 k / r , then
m = 1 n = 1 1 m n | τ m n α β | r = O ( 1 ) i = 1 j = 1 ( i j ) k 1 | a i j | k ( i j ) r / k i r k j β r k 1 log i = O ( 1 ) i = 1 j = 1 i k 1 j k + ( 1 β ) r k 2 log i | a i j | k = O ( 1 ) ,

by using Lemma 2.

(vii) If α = 1 k / r and β > 1 k / r , then
m = 1 n = 1 1 m n | τ m n α β | r = O ( 1 ) i = 1 j = 1 ( i j ) k 1 | a i j | k ( i j ) r / k i r k j r k log i = O ( 1 ) i = 1 j = 1 i k 1 j k 1 log i | a i j | k = O ( 1 ) ,

by using Lemma 2.

(viii) If α > 1 k / r and k / r < β < 1 k / r , then
m = 1 n = 1 1 m n | τ m n α β | r = O ( 1 ) i = 1 j = 1 ( i j ) k 1 | a i j | k ( i j ) r / k i r k j β r k 1 = O ( 1 ) i = 1 j = 1 i k 1 j k + ( 1 β ) r k 2 | a i j | k = O ( 1 ) ,

by using Lemma 2.

(ix) If α > 1 k / r and β = 1 k / r , then
m = 1 n = 1 1 m n | τ m n α β | r = O ( 1 ) i = 1 j = 1 ( i j ) k 1 | a i j | k ( i j ) r / k i r k j β r k 1 log j = O ( 1 ) i = 1 j = 1 i k 1 j k 1 log j | a i j | k = O ( 1 ) ,

by using Lemma 2. □

The one-dimensional version of Theorem 2 appears in [6]. By (5), Theorem 2 includes the following theorem with the special case r = k .

Theorem 3 Let k 1 .

(i) It holds that C ( α , β ) B ( A k 2 ) for each α , β 0 .

(ii) If the condition m = 1 n = 1 m k α 1 n k β 1 | a m n | k = O ( 1 ) is satisfied then C ( α , β ) B ( A k 2 ) for each 1 < α < 0 and 1 < β < 0 .

(iii) If the condition m = 1 n = 1 m k α 1 n k 1 | a m n | k = O ( 1 ) is satisfied then C ( α , β ) B ( A k 2 ) for each 1 < α < 0 and β 0 .

(iv) If the condition m = 1 n = 1 m k 1 n k β 1 | a m n | k = O ( 1 ) is satisfied then C ( α , β ) B ( A k 2 ) for each α 0 and 1 < β < 0 .

Remark 1 Theorem 3 moderates Theorem 1 of [7]. Since Holder’s inequality is valid if each of the terms is nonnegative, it should be added the absolute values of the binomial coefficients in the proof of Theorem 1 of [7], when 1 < α < 0 and/or 1 < β < 0 . Therefore, if we replace the binomial coefficients with their absolute values, then the inequality (15) of [7] will be true. So, we should add the conditions, given above in (ii), (iii) and (iv) of Theorem 3 in the statement of Theorem 1 of [7], for the cases 1 < α < 0 and/or 1 < β < 0 .

Corollary 1 Let θ m n α = 1 E m α i = 0 m E m i α 1 s i n = C ( α , 0 ) ( s m n ) .

(i) It holds that C ( α , 0 ) B ( A k 2 ) for each α 0 .

(ii) If the condition m = 1 n = 1 m k α 1 n k 1 | a m n | k = O ( 1 ) is satisfied then C ( α , 0 ) B ( A k 2 ) for each 1 < α < 0 .

Corollary 2 Let θ m n β = 1 E n β j = 0 n E n j β 1 s m j = ( C , 0 , β ) ( s m n ) .

(i) It holds that C ( 0 , β ) B ( A k 2 ) for each β 0 .

(ii) If the condition m = 1 n = 1 m k 1 n k β 1 | a m n | k = O ( 1 ) is satisfied then C ( 0 , β ) B ( A k 2 ) for each 1 < β < 0 .

Corollary 3 Let σ m n = 1 ( m + 1 ) ( n + 1 ) i = 0 m j = 0 n s i j = ( C , 1 , 1 ) ( s m n ) . Then C ( 1 , 1 ) B ( A k 2 ) .

Declarations

Acknowledgements

Dedicated to Professor Hari M. Srivastava.

Authors’ Affiliations

(1)
Department of Mathematics, Faculty of Arts and Sciences, İstanbul Commerce University

References

  1. Rhoades BE: Absolute comparison theorems for double weighted mean and double Cesàro means. Math. Slovaca 1998, 48: 285–301.MathSciNetGoogle Scholar
  2. Savaş E, Rhoades BE: An inclusion theorem for double Cesàro matrices over the space of absolutely k -convergent double series. Appl. Math. Lett. 2009, 22: 1462–1466. 10.1016/j.aml.2009.03.015MathSciNetView ArticleGoogle Scholar
  3. Flett TM: On an extension of absolute summability and some theorems of Littlewood and Paley. Proc. Lond. Math. Soc. 1957, 7: 113–141. 10.1112/plms/s3-7.1.113MathSciNetView ArticleGoogle Scholar
  4. Chow HC: Note on convergence and summability factors. J. Lond. Math. Soc. 1954, 20: 459–476.View ArticleGoogle Scholar
  5. Mehdi MR: Summability factors for generalized absolute summability. Proc. Lond. Math. Soc. 1960, 10: 180–200. 10.1112/plms/s3-10.1.180MathSciNetView ArticleGoogle Scholar
  6. Şevli H, Savaş E: On absolute Cesàro summability. J. Inequal. Appl. 2009., 2009: Article ID 279421Google Scholar
  7. Savaş E, Şevli H, Rhoades BE: On the Cesàro summability of double series. J. Inequal. Appl. 2008., 2008: Article ID 257318Google Scholar

Copyright

© Şevli and Savaş; licensee Springer. 2013

This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.